The Effect of Profitability, Leverage, and Company Size on Earnings Per Share of Property and Real Estate Companies on the IDX Main Board for the 2021-2024 Period - Evi Maria (LP2M IAIN Palopo, 2026)
This study analyzes the effect of profitability, leverage, and company size on company value using a quantitative approach. This type of research is quantitative research with descriptive and associative methods. The data used are secondary data in the form of financial reports of manufacturing companies listed on the Indonesia Stock Exchange during a certain period. Sampling was carried out using a purposive sampling technique, resulting in a number of companies that meet the research criteria for further analysis. The data analysis method used is SEM PLS with partial and simultaneous hypothesis testing to evaluate the significance of the influence of independent variables on the dependent variable. The results of the study indicate that profitability has a positive and significant influence on company value, while leverage shows a significant negative influence and company size has a significant positive influence.